Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/pas.0000000000001949
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic and Familial Adenomatous Polyposis-associated Foveolar-type Adenoma of the Stomach

Abstract: Gastric foveolar-type adenoma (FA) is a rare benign neoplasm occurring either sporadically or in patients with familial adenomatous polyposis (FAP). However, the molecular features of FA and the relationship between sporadic and syndromic lesions remain unclear. In this study, we performed clinicopathological, immunohistochemical, and genetic analyses of 18 sporadic and 30 FAP-associated FAs. Most sporadic and FAP-associated FAs were located in the upper or middle third of the stomach, on a background of fundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Recently, Kushima suggested that gastric foveolar-type tumors of H. pylori-uninfected cases should be called "foveolar-type adenoma", since those are clinically and molecularpathologically different from the tumors of H. pyloripositive cases. (28,29). Therefore, the present study was conducted to analyze the prevalence of raspberry-type gastric foveolar-type tumor without division into adenocarcinoma or adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kushima suggested that gastric foveolar-type tumors of H. pylori-uninfected cases should be called "foveolar-type adenoma", since those are clinically and molecularpathologically different from the tumors of H. pyloripositive cases. (28,29). Therefore, the present study was conducted to analyze the prevalence of raspberry-type gastric foveolar-type tumor without division into adenocarcinoma or adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…An FGA is an epithelial polyp consisting of neoplastic foveolar epithelium that occurs in the oxyntic compartment, and positive for MUC5AC (gastric foveolar mucin, gastric phenotype marker). This tumor primarily shows small reddish protrusions (raspberry type) and rarely those with a whitish at form ( at type) [5,7,18,19]. An IGD is an epithelial neoplasm consisting of dysplastic intestinalized epithelium that occurs as a depressed lesion in the pyloric-gland mucosa, and positive for CDX2 (intestinal differentiation marker), MUC2 (goblet cell mucin, intestinal phenotype marker), and/or CD10 (glycosylated transmembrane protein, intestinal phenotype marker) [6].…”
Section: Histologic Characteristics and Pathological Stagingmentioning
confidence: 99%
“…We have previously reported that sporadic foveolar-type adenoma (FA) occurring on nonatrophic mucosa includes 2 distinct subtypes, namely, flat FA and raspberry-like FA, with each exhibiting a characteristic appearance on endoscopy. 1 These 2 subtypes are clinicopathologically and genetically different; specifically, while flat FAs consistently harbor APC and KRAS mutations, raspberry-like FA lacks them. Remarkably, despite distinct clinical backgrounds, familial adenomatous polyposis (FAP)-associated FAs share genetic features with sporadic, flat FAs.…”
Section: Klf4 Ca1322c Mutation Is a Consistent And Specific Genetic F...mentioning
confidence: 99%
“…1). 1 Histologic diagnoses of intestinal-type adenoma or pyloric gland adenoma were based on the WHO classification 5,6. Dysplasia and intramucosal adenocarcinoma were diagnosed according to the previously reported criteria,7 and dysplasia was further classified as foveolar-type, intestinal-type, or hybrid-type based on previously described morphologic features 8.…”
mentioning
confidence: 99%